The impact of smoking on sexual function - Mima, Mahmoud; Huang, Jason B.; Andriole, Gerald L.; Freedland, Stephen J.; Ohlander, Samuel J.; Moreira, Daniel M. (BJU international, 2022)
Objectives To evaluate the hypothesis that there is an improvement in sexual function following smoking cessation (as smoking is a well‐established risk factor for sexual dysfunction), we analysed the association between cigarette smoking and smoking cessation with sexual function among participants of the REduction by DUtasteride of prostate Cancer Events (REDUCE) study. Subjects and Methods We analysed baseline data of 6754 men, aged 50–75 years divided into: lifelong non‐smokers, former smokers, and current smokers. We examined total testosterone (TT, normal range ≥10 nmol/L) and sexual function variables: self‐reported sexual activity, low libido, and erectile dysfunction (ED). Differences between current vs non‐smokers and former vs current smokers were analysed using the chi‐square test, linear and logistic regressions. Results A total of 3069 (45.4%) men were non‐smokers, 2673 (39.6%) former smokers, and 1012 (15%) current smokers. Current smokers were significantly younger than former and non‐smokers (mean age 61.6, 63.2, and 62.7 years, respectively), leaner (mean body mass index 27.0, 27.7, and 27.2 kg/m2, respectively), and had less hypertension (32.4%, 41.6%, and 36.8%, respectively; all P < 0.01). In uni‐ and multivariable analysis, current smokers had higher mean TT than non‐smokers (485.4 vs 451.2 nmol/L, P < 0.001), higher prevalence of low libido (25.6% vs 21.0%, P = 0.002) and ED (31.6% vs 26.0%, P < 0.001) with comparable sexual activity (81.7% vs 82.8%, P = 0.420). In multivariable analysis, former smokers had statistically significantly less prevalence of low libido (odds ratio [OR] 0.8, P = 0.013) and ED (OR 0.8, P = 0.006) compared to current smokers. Conclusion Cigarette smoking was associated with worse sexual health compared to non‐smokers, while former smokers had better erectile function and libido than current smokers. Smoking cessation may improve male sexual health and counselling on smoking cessation may be considered at the time of sexual health evaluations.